The Effect Of Antiporcine Willebrand Factor Monoclonal Antibodies On The Bleeding Time - Bowie, E J W; Fass, D N; Katzmann, J A (Thrombosis and Haemostasis, 1981)
Murine monoclonal antibodies to porcine Willebrand factor were used to study the role of Willebrand factor in hemostatic plug formation in the in vivo and in vitro skin bleeding times. The in vivo assay requires the intravenous injection of antibody-containing mouse ascitic fluids into normal animals with subsequent ear bleeding time tests performed over a 24-hour period. The in vitro assay was carried out with heparinized normal porcine blood flowing through a 0.5 cm incision in an excised piece of porcine skin. The heat inactivated ascitic fluids, containing the antibodies, were used ;Ln these assays at final dilutions of 2 × 102 through 2 × 105 The 7 antibodies used comprised at least 5 groups with differing reactivities based on assays other than bleeding time tests. The antibody titers in a poreineg Willebrand factor-binding radioimmunoassay ranged from 108 through 1012 . Doses of 10HL of ascitic fluid/kg of body weight (approximately 2 × 103 final dilution) were able to transiently prolong the in vivo bleeding time without alteration of other VIII complex values (VIII:C, ristocetin cofactor activity and Vlll-related antigen). Higher doses resulted in bleeding times similar to von Willebrand pigs (>15 min) immediately following infusion, with a decay of the effect over the next 2 hours. At dilutions of 2 × 104 selected monoclonal antibodies interfered with hemostasis in the in vitro model whereas other antibodies inhibited only at 2 × 102 dilution. With one exception, the potencies of the antibodies appeared to be similar in both assays. The titer of the antibodies in the radioimmunoassay does not appear to correlate with prolongation of the in vitro bleeding time, suggesting specific reactivity with functional sites involved in hemostatic plug formatio.